Assessment of Interleukin 1-β, Interleukins -6 and Some Biochemical Parameters in a Sample of Iraqi Patients with β –Thalassemia Major - Mohammed, Ammar J.; Yenzeel, Jabbar H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Sixty patients (male and female) with β-thalassemia major and thirty healthy subjects were enrolled in this study during their attendance at "Abin AL-Baladi Hospital in Baghdad" from September 2022 to January 2023. All patients and healthy subjects ranged in age from 15 to 30 years, and we collected the necessary data with their consent, adhering to the College of Science's ethics (CSEC/0922/0104 in 2022/9/28). Venous blood was collected and divided into two parts: the first part for the determination of CBC, and the second part was allowed to coagulate for serum separation to measure the level of C-reactive protein, ferritin, and pro-inflammatory cytokines like interleukin-1β and interleukin-6 by using the ELISA Kit. The results showed a highly significant (p≤0.01) decrease in RBC count and hemoglobin (3.03 ±0.06 106/µL and 8.01 ±0.17 Hg/dl) respectively in β-thalassemia patients in compare with control group (4.77 ±0.07 106/µL and 14.06 ±0.24 Hg/dL) respectively, while there was a highly significant (p≤0.01) increase in the platelets count (384.59 ±21.67 10^3/µL) in patients compared with control (224.06 ±6.23 10^3/µL); furthermore, ferritin and CRP showed highly significant (p≤0.01) increase (4910.15 ±202.67 ng/ml, and 3.02 ±0.08 µg/ml) respectively in patients compared with control (284.91 ±16.78 ng/ml, and 1.178 ±0.03 µg/ml) respectively. Also, there was a highly significant (P≤0.01) increase in IL-1β and IL-6, which were 284.19 ±4.29 pg/ml and 27.92 ±0.97 pg/ml, respectively, in patients in comparison with control (142.09 ±0.70 pg/ml and 11.43 ±0.32 pg/ml), respectively. From the above findings, it can be concluded that proinflammatory cytokines have a significant impact on the progression and pathology of the disease.